Comparative Analysis of Muscle Elasticity and Pathological Characteristics Between Affected and Unaffected Sides in Postherpetic Neuralgia Patients: Protocol for a Pilot Cohort Trail - Ji H; Ma J; Cui X; Huang Y (Journal of Pain Research)
Heyu Ji,1 Jiangyu Ma,2 Xulei Cui,1 Yuguang Huang1 1Department of Anesthesiology, Peking Union Medical College Hospital, Chinese Academy of Medical Science and Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Nuclear Medicine, Peking Union Medical College Hospital, Chinese Academy of Medical Science and Peking Union Medical College, Beijing, People’s Republic of ChinaCorrespondence: Xulei Cui; Yuguang Huang, Department of Anesthesiology, Peking Union Medical College Hospital, Shuaifuyuan 1st, Dongcheng District, Beijing, 100730, People’s Republic of China, Email cuixulei10685@pumch.cn; garypumch@163.comBackground: Postherpetic neuralgia (PHN) is the most common condition that can develop as a complication after herpes zoster (HZ) infection, characterized by pain that persists for more than 3 months after the initial rash has resolved. In most patients with HZ, the rash appears unilaterally. While the treatment of PHN is primarily focused on neural mechanisms due to HZ’s neurotropism nature, recent evidence suggests that muscle tissues within the affected regions may also experience pathological changes that contribute to the pain. These changes could reveal novel therapeutic targets and enhance patient prognosis. This study aims to investigate these muscular changes and explore myogenic pain mechanisms in PHN patients. It employs ultrasound elastography to compare muscle elasticity between the affected and unaffected sides and conduct muscle biopsies for pathophysiological analysis to uncover the underlying mechanisms.Materials and Methods: This comparative cross-sectional study aims to enroll 30 PHN patients. The primary outcome is the comparison of muscle elasticity on the affected sides with unaffected sides. The secondary outcome is from muscle biopsies, which are obtained and analyzed by histopathological techniques. Pain levels before and after therapy are assessed using the Numerical Rating Scale (NRS), with follow-up to evaluate outcomes and satisfaction. Statistical analysis will employ paired t-tests or Wilcoxon signed-rank tests to compare muscle elasticity, and correlation analysis to explore the relationship between elasticity and pathological findings.Hypothesis: The study hypothesis is that muscle elasticity on the affected side is significantly higher than on the unaffected side, with the coexistence of myofascial pain. This myofascial pain may overlap with PHN pain and may be a source of discomfort in refractory PHN cases. Furthermore, muscle biopsies are conducted to clarify pathological changes. This study may pave the way for novel treatment strategies for PHN and establish a foundation for future research.Study Registration: This study has obtained ethical approval from the Institutional Review Board of Peking Union Medical College Hospital on 28 August 2023 (I-23PJ1409) and is registered at ClinicalTrails.gov. Written informed consent has been obtained from all participants.Keywords: postherpetic neuralgia, shear wave elastography, myofascial pain, muscle biopsy